The Dual-Specificity LAMMER Kinase Affects Stress-Response and Morphological Plasticity in Fungi - Lim, Joo-Yeon; Park, Hee-Moon (Frontiers in Cellular and Infection Microbiology, 2019)
The morphological plasticity of fungal pathogens has long been implicated in their virulence and is often influenced by extracellular factors. Complex signal transduction cascades are critical for sensing stresses imposed by external cues such as antifungal drugs, and for mediating appropriate cellular responses. Many of these signal transduction cascades are well-conserved and involve in the distinct morphogenetic processes during the life cycle of the pathogenic fungi. The dual-specificity LAMMER kinases are evolutionarily conserved across species ranging from yeasts to mammals and have multiple functions in various physiological processes; however, their functions in fungi are relatively unknown. In this review, we first describe the involvement of LAMMER kinases in cell surface changes, which often accompany alterations in growth pattern and differentiation. Then, we focus on the LAMMER kinase-dependent molecular machinery responsible for the stress responses and cell cycle regulation. Last, we discuss the possible cross-talk between LAMMER kinases and other signaling cascades, which integrates exogenous and host signals together with genetic factors to affect the morphological plasticity and virulence in fungi.